Spatiotemporal characteristics and meteorological driving factors of flash droughts in the Yellow River Basin, China - Dehe Xu; Menglong Wang; Qi Zhang; Shiwen Wu; Linjing Zhang (Ecological Indicators)
Flash droughts, characterized by rapid onset, rapid intensification, and severe environmental and socioeconomic impacts, have exhibited a rising global trend amid climate change. However, their spatially heterogeneous drivers remain insufficiently understood. The objective of this study is to examine the spatiotemporal characteristics of flash droughts and to reveal the spatial variability of their meteorological drivers in the Yellow River Basin (YRB). Flash droughts were identified based on soil moisture percentile thresholds and decline rates. Theil-Sen slope and Mann-Kendall tests were used to analyze trends. The Geographically Weighted Regression (GWR) model was applied for the first time to assess spatial variations in meteorological influences on drought duration. Key findings are as follows:(1) Flash droughts in the YRB occurred with an average annual frequency of 4,161.6 events and a mean duration of 7.7 pentads, indicating widespread occurrence across the region. (2) The proportion of the basin affected by flash droughts increased significantly at a rate of 0.1 per decade (p < 0.05), with 76.8 % of the area showing increasing trends in frequency and 64.2 % exhibiting extended durations. (3) The GWR model revealed pronounced spatial heterogeneity in meteorological drivers influencing drought duration. (4) Precipitation was identified as the dominant driver in 42.2 % of the region, followed by temperature (24.1 %) and evapotranspiration (15.6 %), with regression coefficients varying considerably across space. These findings improve understanding of flash drought mechanisms in the YRB and provide a scientific basis for region-specific water resource management and drought mitigation strategies.